A Noninvasive and Speculative Method of Visualizing Latent Fingerprint Deposits on Thermal Paper. Issue 4 (31st March 2015) - Bond, John W.
Abstract Latent fingerprint deposits on thermal paper have been visualized noninvasively at visible wavelengths when illuminated with a UV‐A light source (peak 365 nm). A higher intensity UV source (250 W/m2 at 0.38 m) gave superior fingerprint visibility when compared with a 60 W/m2 (at 0.4 m) source. Removing the visible (blue) component of the light source emission did not adversely affect the visibility of the fingerprint. Sample fingerprints from 100 donors, when examined 24 h after deposition, produced identifiable fingerprints from nearly 34% of fingerprint deposits. A mechanism for the observed visibility is proposed based on low emission of visible wavelengths from areas of thermal paper coincident with the fingerprint deposit, when illuminated with UV. This is likely due to a weak color change in the thermal paper dye arising from protonated amino acid components of the sweat. This effect was not observed on nonthermal paper.